2D Cellular Automata with an Image Processing Application - Uguz, S.; Sahin, U.; Siap, I.; Akin, H. (POLISH ACAD SCIENCES INST PHYSICS, 2014)
This paper investigates the theoretical aspects of two-dimensional linear cellular automata with image applications. We consider geometrical and visual aspects of patterns generated by cellular automata evolution. The present work focuses on the theory of two-dimensional linear cellular automata with respect to uniform periodic and adiabatic boundary cellular automata conditions. Multiple copies of any arbitrary image corresponding to cellular automata find so many applications in real life situation e.g. textile design, DNA genetics research, etc.
Keywords: Physics